High Rate of Chronic Villitis in Placentas of Pregnancies Complicated by Influenza A/H1N1 Infection - Wouter J. Meijer; Annemarie M. J. Wensing; Hein W. Bruinse; Peter G. J. Nikkels (Hindawi Limited, 2014)
Introduction. Pandemic influenza A/H1N1 infection during pregnancy has a negative impact on several aspects of pregnancy outcome. As yet, no elucidating mechanism has been revealed for these effects. We investigated whether placentas of pregnancies complicated by 2009 influenza A/H1N1 infection demonstrated an increased rate of chronic villitis and whether this villitis was caused by influenza virus. Methods. We performed a cohort study on 145 pregnant outpatients during the 2009-2010 influenza A H1N1 pandemic. The placentas of patients with influenza infection were examined for histologic signs of chronic villitis. In case of villitis, polymerase chain reaction (PCR) on influenza virus was performed on placental tissue. Results. 29 patients had influenza infection. Placentas of 15 of these patients were collected and examined. In 7 cases (47%) chronic villitis was detected. Placental weight and birth weight of the neonates did not differ between cases with and without chronic villitis. In all cases PCR was negative for influenza. Conclusion. In our series, chronic villitis was present in a high proportion of placentas of pregnancies complicated by 2009 influenza A/H1N1 infection. We could not demonstrate the presence of influenza virus in placental tissue.